If b is the harmonic mean between a and c, prove that ;1/b-a + 1/b-c=1/a+1/c.
Asked by | 6th Jul, 2008, 11:29: PM
since b is H.M. of a and c so 2/b= 1/a +1/c
so R.H.S. = 2/b
in L.H.S. = ( 2b-a-c ) / (b2 - (a+c)+ac )
now put b= 2ac /(a+c) and simplify it
you will get the same thing.
Hence the given relation is proved.
Answered by | 10th Aug, 2008, 08:56: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number